The Interactive Effect between Fermentation with Trichoderma reesei on Ammoniation on Fiber Component of Sugar Palm Pulp - Nurul Husnah Febrianti; Agung Subrata; Joelal Achmadi (LPPM Perjuangan University of Tasikmalaya, 2020)
The purpose of this research was to examine the combination effect of fermentation time by Trichoderma reesei and ammoniation on fiber component of sugar palm pulp. The research used sugar palm pulp from Boyolali which was sun-dried. Sugar palm pulp fermentation with Trichoderma reesei requires nitrogen for microbial growth. Ammoniation process could loose lignocellulosic bonds and provides the nitrogen supply for Trichoderma reesei, therefore these treatments could optimize Trichoderma reesei in the fermentation process. Samples were fermented for 0, 3 and 6 days with 1,5% Trichoderma reesei. The research treatments were allocated according to a completely randomize design with pattern of 2x3 factorial. First factor was ammoniation treatment and second factor was variation of fermentation time. The parameters observedd were NDF, ADF, hemicellulose, cellulose and lignin. Research result showed that there is was no interactive effect between treatments on reducing levels of NDF and ADF, but interaction treatments decreased (P<0.05) levels of, cellulose and lignin. In conclusion, the interactive effet between fermentation time with Trichoderma reesei and ammoniation reduce levels of hemicellulose, cellulose and lignin in sugar palm pulp.